Biochemical composition of refluxate in saliva and gastric juice in patients with physiological cardia insufficiency and hiatal hernias under martial law conditions - O.M. Babii; A.M. Halinska; N.V. Prolom; О.О. Halinskyi (Gastroenterologìa)
Background. A hiatal hernia (HH) and functional cardia insufficiency lead to changes in the biochemical composition of gastric juice and saliva, affecting the course of reflux disease and the condition of the mucous membrane. The study of biochemical markers such as pepsin, bile acids, total calcium, and nitric oxide (NOx) allows for a more accurate diagnosis of reflux types, assessment of the degree of mucosal damage, and identification of the diseases pathogenesis features in both military (MP) and non-military personnel (NMP). This will contribute to the development of optimal approaches to diagnosis and treatment. Objective: to assess the biochemical composition of refluxate in hiatal hernias under martial law conditions by examining saliva and gastric juice. Materials and methods. The study was conducted among 66 patients divided by the types of HH: 30 military personnel: type I — axial HH (n = 11), type II — paraesophageal HH (n = 19); and 36 NMP: type I — axial HH (n = 22), type II — paraesophageal HH (n = 14). Biochemical analyses of saliva and gastric juice included pH measurement, determination of pepsin, bile acids, total calcium, and NOx levels. Results. MP with HH had an increase in pH and a decrease in pepsin concentration, indicating hypoacidity. In NMP with HH type I, these changes were more pronounced. The content of bile acids in gastric juice was elevated in all groups, particularly in MP with HH type II, indicating alkaline reflux. A significant increase in bile acid concentration was observed in the saliva of MP, which is a marker of aggressive reflux, whereas in NMP, pH levels changed more prominently, along with a reduction in pepsin. NOx content in MP with HH type II significantly exceeded control values, indicating active inflammatory processes. Conclusions. The results obtained confirm that among participants with physiological cardia insufficiency in HH, the composition of refluxate, the mechanisms and clinical features of reflux disease were different depending on the HH type and the professional status of the patient. Alkaline refluxate, high nitric oxide and total calcium concentrations are the dominant features of HH type II, especially in MP, whereas acidic refluxate was more commonly observed in MP with physiological cardia insufficiency in HH type I. This highlights the necessity of an individualized approach to the diagnosis and treatment of patients based on refluxate composition.